Majapahit Marine Park Development Policy on the Socio-Economic Life of the Mojokerto City Community - Muhaimin, Hikmah; Herachwati, Nuri; Hadi, Cholicul; Suhariadi, Fendy; Mudzakkir, Mohammad Fakhruddin (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
This research is motivated by Presidential Regulation of the Republic of Indonesia Number 80 of 2019 concerning the acceleration of economic development in the Gresik-Bangkalan-Mojokerto-Surabaya-Sidoarjo-Lamongan, Bromo-Tengger-Semeru, and Selingkar Wilis and Lintas Selatan regions. To support this regulation, the Mojokerto City Government developed a Tourist Attraction (DTW) which is regulated in Mojokerto City Regulation Number 7 of 2021 concerning the Regional Medium-Term Development Plan for 2018-2023. This tourism development includes the Majapahit Marine Park (TBM), Mojopahit restaurant, PLUT, IKM Center, and road access to tourist locations. This study aims to analyze the impact of the Majapahit Marine Park (TBM) development policy on the socio-economic life of the community in Blooto Village, Mojokerto City. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that the construction of TBM causes physical changes that have an impact on the social and economic aspects of the community. In the social aspect, there is a change in community behavior and an increase in the economy, seen from the buying and selling activities of the surrounding community which have been predicted because of the existence of the tourist attraction. This positive impact supports regional economic growth. In addition, there is a change in the physical environment, such as the area around the Rejoto bridge which is now more crowded after previously only functioning as a connection between sub-districts.gb777